Comparing dose prediction software used to manage gentamicin dosing. Issue 5 (14th May 2013) - Wong, C.; Kumar, S. S.; Graham, G. G.; Begg, E. J.; Chin, P. K. L.; Brett, J.; Ray, J. E.; Marriott, D. J. E.; Williams, K. M.; Day, R. O.
Abstract Background Current Australian guidelines recommend initiating directed therapy of gentamicin if administration exceeds 48 h. Directed doses of gentamicin require the monitoring of plasma concentrations of gentamicin to determine the 24‐h area under the time course of plasma gentamicin concentrations (AUC) and a dosage prediction program, for example TCIWorks or Aladdin. However, doses calculated by such programs have not been compared with an established program. Aim To compare the directed dosage of gentamicin calculated by TCIWorks, Aladdin and an Excel‐based program, with an established program, Abbottbase. Methods Peak and trough plasma concentrations after the first and second administered doses of gentamicin were available from three patient groups (n = 20–23) with varying creatinine clearances (<40, 40–80, >80 mL/min). The directed dose needed to produce 24‐h AUC values of 80 mg.h/L was calculated using each program. Results There was a strong correlation between the directed doses predicted by each of the three programs compared with Abbottbase, following the first administered dose (r2 > 0.97, P < 0.0001). The mean ratio (90% confidence intervals) of these directed doses of the gentamicin were: TCIWorks/Abbottbase 106% (105–107%), Aladdin/Abbottbase 102% (101–103%) and Excel/Abbottbase 108% (106–109%). The correlations and dose ratios were also similar when comparisons were made following the second administered dose. For each of the three renal function groups, all programs yielded similar directed doses. Conclusions The four programs used in the calculation of directed doses of gentamicin yielded similar results. Any would be suitable for use in clinical practice.